The official Cambridge guide to IELTS : for academic & general training : student's book with answers - Cullen, Pauline; French, Amanda; Jakeman, Vanessa (New York Cambridge University Press, 2014)
Cambridge English bring you this definitive guide, from our team of highly respected and experienced writers.Practical and easy to use, it focusses on the language and skills you need to perform with confidence
'The official Cambridge guide to IELTS' is THE definitive guide to IELTS. It contains all you need to succeed in the exam. Skill-building exercises cover all of the question types in the exam for both the General Training and Academic modules. Our research into real IELTS candidates' exam answers - and the mistakes they make, helps you avoid the same ones! Eight official practice tests and a focus on test-taking strategy help you maximise your score. The DVD-ROM includes videos of the Speaking test, and all the listening material, including the tests, as MP3 files
Student's Book With Answers
1 11 12 13
Keywords: English language -- Problems, exercises, etc; Ielts Reading Skills; Ielts Speaking; Ielts Writing; International English Language Testing System -- Study guides; Language -- Examination Questions; Study guides